2022
DOI: 10.1093/heapol/czac058
|View full text |Cite
|
Sign up to set email alerts
|

Moving the Brazilian ischaemic stroke pathway to a value-based care: introduction of a risk-adjusted cost estimate model for stroke treatment

Abstract: The unsustainable increases in healthcare expenses and waste have motivated the migration of reimbursement strategies from volume to value. Value-based health care requires detailed comprehension of cost information at the patient level. This study introduces a clinical risk- and outcome-adjusted cost estimate model for stroke care sustained on time-driven activity-based costing (TDABC). In a cohort and multicenter study, a TDABC tool was developed to evaluate the costs per stroke patient, allowing us to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Regarding the use of electronic data in healthcare, one systematic review in 2017 identified a study where the process maps were created based on electronic medical records involving surgeries and medical care procedures [ 3 ]. In our review, the electronic medical records were used to construct the process maps identified in 23 studies [ 5 , 16 , 22 , 24 26 , 29 , 32 , 34 , 36 , 43 , 47 , 48 , 58 , 59 , 61 , 66 , 74 , 75 , 77 , 78 , 82 , 84 ], proving that using medical data from electronic medical records has enhanced and provided support to the process.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Regarding the use of electronic data in healthcare, one systematic review in 2017 identified a study where the process maps were created based on electronic medical records involving surgeries and medical care procedures [ 3 ]. In our review, the electronic medical records were used to construct the process maps identified in 23 studies [ 5 , 16 , 22 , 24 26 , 29 , 32 , 34 , 36 , 43 , 47 , 48 , 58 , 59 , 61 , 66 , 74 , 75 , 77 , 78 , 82 , 84 ], proving that using medical data from electronic medical records has enhanced and provided support to the process.…”
Section: Discussionmentioning
confidence: 87%
“…Regarding the other types of construction, we identified the process maps of a study performed in Canada that created a model for a clinical pathway of a patient submitted to a routine outpatient endoscopic sinus surgery for estimating the cost of this procedure on the patient [ 72 ]. In a study performed in Brazil, five main perspectives were analyzed, and the process maps were complemented by the clinical analysis of the protocols in the ischemic stroke condition [ 61 ]. The details of how the process maps were constructed in each study are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten countries are participating in this venture, utilizing real-world data to examine the costs associated with patient resource consumption. The methodology used for this project was based on prior studies conducted in Brazil, two of which yielded financial information for the implementation of mechanical thrombectomy in public healthcare systems [22,23], and another introduced a risk-adjusted cost estimate model to sustain the redesign of a reimbursement strategy based on value specific for the ischemic stroke pathway [24]. The experience from those previous projects highlighted the value of having accurate and real-world about patients' resource consumption from the healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, monitoring more accurate stroke cost information and clinical outcomes are of utmost importance to establish trust in value agreements to a highly prevalent disease. Technological advances allowing healthcare systems to estimate costs similar to the one created in Brazil [24] might facilitate a solution to the health cost crisis.…”
Section: Discussionmentioning
confidence: 99%